A case of pulmonary lymphangioleiomyomatosis complicated with uterine and retroperitoneal tumors. (2015) - Numata, Takanori; Araya, Jun; Mikami, Jiro; Hara, Hiromichi; Harada, Tohru; Takahashi, Hiroyuki; Nakayama, Katsutoshi; Kuwano, Kazuyoshi
Abstract: A 39-year-old female experienced dyspnea on exertion for eight months. Chest CT demonstrated findings of Lymphangioleiomyomatosis (LAM), including diffuse thin-walled cystic lesions. A surgical lung biopsy revealed human melanoma black-45-positive cell infiltration and aggregation, resulting in a diagnosis of sporadic LAM without tuberous sclerosis complex. Pelvic MRI showed two large tumors, one of which was in the myometrium and the other was in the retroperitoneal space. Because we were not able to exclude the presence of malignant tumors using MR imaging, the tumors were surgically resected. The histopathology demonstrated the resected tumors to be composed of LAM cells. The patient's symptoms worsened, and sirolimus was administered, which improved the dyspnea and pulmonary function. The adverse effect was mild liver damage. Following the initiation of treatment with sirolimus, transient elevation of the serum KL-6 level was detected without interstitial pneumonia. This LAM case complicated with large uterine and retroperitoneal tumors was successfully treated with surgical resection and sirolimus.